Penanganan dan Analisa Kegagalan Pada Bleed Air Leak Detection System Pesawat Airbus A330-300 di Hanggar 3 PT.GMF AEROASIA - Agung Prakoso; Riski Kurniawan; Farchan Mauluddin (Politeknik Negeri Batam, 2021)
The bleed air leak detection system on aircraft is used to detect a leak in the bleed air duct. This system can detect over heat temperature outside of the duct if there is a leak around the duct. Bleed air leak detection is equipped with a sensing element to detect the rise of temperature because of the leak around the bleed air duct. These sensing elements are installed on the engine pylon, wing and fuselage. The rise of temperature detected by the sensing element can be monitored on the bleed monitoring computer (BMC) and then will be forwarded to the engine bleed switch in the cockpit. Troubleshooting Manual (TSM) Task 36-22-00-810-911-A is used to solve bleed air leak detection system problems. The fault tree analysis method is also used to obtain the possible causes of failure in the bleed air leak detection system. In this study found damage to the sensing element in zone 71 HF. The sensing element has been used for 24 years and 8 months from that set by the manufacturer, which is 25 years, so it is necessary to replace it with a new sensing element. Based on the fault tree analysis results, several possible causes of the bleed air leak detection system failure were obtained, such as electorstatic, short circuit, lost continuity, connector fault, control logic fault, thermistor disconnected, performance degradation, component dislocation, and corrosion.